Outcomes of Operative and Nonoperative Treatment for Adult Spinal Deformity: A Prospective, Multicenter, Propensity-Matched Cohort Assessment With Minimum 2-Year Follow-up. Issue 6 (June 2016) - Smith, Justin S.; Lafage, Virginie; Shaffrey, Christopher I.; Schwab, Frank; Lafage, Renaud; Hostin, Richard; O'Brien, Michael; Boachie-Adjei, Oheneba; Akbarnia, Behrooz A.; Mundis, Gregory M.; Errico, Thomas; Kim, Han Jo; et al.
Abstract : BACKGROUND: High-quality studies that compare operative and nonoperative treatment for adult spinal deformity (ASD) are needed. OBJECTIVE: To compare outcomes of operative and nonoperative treatment for ASD. METHODS: This is a multicenter, prospective analysis of consecutive ASD patients opting for operative or nonoperative care. Inclusion criteria were age >18 years and ASD. Operative and nonoperative patients were propensity matched with the baseline Oswestry Disability Index, Scoliosis Research Society-22r, thoracolumbar/lumbar Cobb angle, pelvic incidence–to–lumbar lordosis mismatch (PI-LL), and leg pain score. Analyses were confined to patients with a minimum of 2 years of follow-up. RESULTS: Two hundred eighty-six operative and 403 nonoperative patients met the criteria, with mean ages of 53 and 55 years, 2-year follow-up rates of 86% and 55%, and mean follow-up of 24.7 and 24.8 months, respectively. At baseline, operative patients had significantly worse health-related quality of life (HRQOL) based on all measures assessed ( P < .001) and had worse deformity based on pelvic tilt, pelvic incidence–to–lumbar lordosis mismatch, and sagittal vertical axis ( P ⩽ .002). At the minimum 2-year follow-up, all HRQOL measures assessed significantly improved for operative patients ( P < .001), but none improved significantly for nonoperative patients except for modest improvements in the Scoliosis Research Society-22r pain ( P = .04) and satisfaction ( P < .001) domains. On the basis of matched operative-nonoperative cohorts (97 in each group), operative patients had significantly better HRQOL at follow-up for all measures assessed ( P < .001), except Short Form-36 mental component score ( P = .06). At the minimum 2-year follow-up, 71.5% of operative patients had ≥1 complications. CONCLUSION: Operative treatment for ASD can provide significant improvement of HRQOL at a minimum 2-year follow-up. In contrast, nonoperative treatment on average maintains presenting levels of pain and disability. ABBREVIATIONS: ASD, adult spinal deformity HRQOL, health-related quality of life LL, lumbar lordosis MCID, minimal clinically important difference NRS, numeric rating scale ODI, Oswestry Disability Index PI, pelvic incidence SF-36, Short Form-36 SRS-22r, Scoliosis Research Society-22r SVA, sagittal vertical axis